Understanding Public Perceptions of Mosquito-Related Information Sources and Adapting Research Findings to the Needs of Industry Professionals - Shelli Rampold; Ricky Telg; Alena Poulin; Sandra Anderson; Angela B. Lindsey; Ashley McLeod-Morin; Phillip Stokes (EDIS, 2020)
The Prevent & Protect publication series focuses on the creation of different material formats to resonate with various audiences and ways to maximize their efficacy in communicating risk to the public about mosquito control. The overview of the Prevent & Protect project, developed by the UF/IFAS Center for Public Issues Education in Agriculture and Natural Resources (PIE Center), can be found in EDIS publication AEC694/WC357, Public Perceptions of Mosquitoes and Mosquito Control. This new 3-page document describes the importance of understanding and adapting to public perceptions of information sources and how scientists can adapt their research findings based upon the needs of professionals in the field to create usable outreach materials. Written by Shelli Rampold, Ricky Telg, Alena Poulin, Sandra Anderson, Angela B. Lindsey, Ashley McLeod-Morin, and Phillip Stokes, and published by the UF/IFAS Department of Agricultural Education and Communication.